Methods of Islamic Religion Teachers in Improving Post-Online Student Learning Motivation at MTs Al-Washliyah 18 Tembung Academic Year 2022-2023 - Nasution, Najmul Akhyar Mahmudi; Mahariah (LP. Ma'arif Janggan Magetan, 2023)
This research aims to be oriented towards describing the methods of Islamic religious education teachers to increase motivation to study Islamic religious education in the post-COVID-19 pandemic period at MTs Al-Washliyah 18 Tembung for the 2022-2023 academic year. This type of research is called qualitative research. To obtain the data needed in this study, it is used in the form of data, either in writing, orally, or in actions observed through observation and interviews. The approach used in this study uses a qualitative descriptive approach; this method utilizes qualitative data and is described descriptively. In this study, the methods applied to learning Islamic religious education were cooperative learning, project-based learning, and interactive multimedia implementation. The selection of the method used is considered based on the backgrounds and learning styles of students in the MTs environment. Al-Washliyah 18 Tembung